2009
DOI: 10.1126/scisignal.2000446
|View full text |Cite
|
Sign up to set email alerts
|

EGFR Signaling Through an Akt-SREBP-1–Dependent, Rapamycin-Resistant Pathway Sensitizes Glioblastomas to Antilipogenic Therapy

Abstract: Glioblastoma, the most common malignant brain tumor, is among the most lethal and difficult cancers to treat. Although epidermal growth factor receptor (EGFR) mutations are frequent in glioblastoma, their clinical relevance is poorly understood. Studies of tumors from patients treated with the EGFRinhibitor lapatinib revealed that EGFR induces the cleavage and nuclear translocation of the master transcriptional regulator of fatty acid synthesis, sterol regulatory element-binding protein 1 (SREBP-1). This respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
331
2
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 299 publications
(350 citation statements)
references
References 36 publications
15
331
2
2
Order By: Relevance
“…SREBP1 also increases reactive oxygen species (ROS) production (101) inducing tumor progression (102). A similar role of progesterone and EGF on SREBP cleavage and expression was reported in breast cancer cells (22,65,67).…”
Section: Implication Of Other Lipogenic Genesmentioning
confidence: 96%
See 1 more Smart Citation
“…SREBP1 also increases reactive oxygen species (ROS) production (101) inducing tumor progression (102). A similar role of progesterone and EGF on SREBP cleavage and expression was reported in breast cancer cells (22,65,67).…”
Section: Implication Of Other Lipogenic Genesmentioning
confidence: 96%
“…High SCD1 expression is associated with cancer cell proliferation (18) and with a decrease in cell death (18)(19)(20)(21). SREBP1c also plays a role in the transformation of normal cells (22).…”
Section: Lipogenesis Tumor Growth and Apoptosismentioning
confidence: 99%
“…Because rapamycin has elicited mostly cytostatic effects in clinical chemotherapy, identifying mechanisms for enhancing the potential tumor-specific cytotoxic effects of rapamycin is an important problem. 10,17 The mixed results in the clinic may be due to inhibition of the negative feedback regulation of Akt, such that some tumors treated with rapamycin or its analogs display increased phosphorylation of Akt. 12 The UCDD compounds reduced Akt phosphorylation, possibly by interfering with upstream activating kinases.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Although rapamycin opposes survival signaling by Akt and mTORC1, rapamycin can also trigger a counter-productive increase in phosphorylation of Akt itself, potentially impairing cytotoxic chemotherapeutic responses to rapamycin in tumor cells. 10,12,17 Because UCDD001 and UCDD002 are cytotoxic for Akt-expressing cells, we sought to determine their efficacy in combination with rapamycin, an Akt-selective chemotherapeutic that has been approved for treatment of renal clear cell carcinoma. 9 At a concentration that is selectively cytotoxic for Akt-dependent cells, UCDD001 enhanced the cytotoxic effect of rapamycin in Akt-expressing cells (Fig.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…Selective targeting of EGFR hyperactive glioblastomas can, thus, be achieved by inhibition of these repair process. Other groups have demonstrated that EGFR hyperactivation in glioblastoma cell lines heightens requirement for lipogenesis 30,31 . Other examples of such critical non-oncogenic pro-survival functions required for maintenance of the tumorigenic state include dependency on mechanism for compensating mitotic and proteotoxic stress and interplay with the tumor microenvironment including the immune system 26 .…”
Section: Concept 3: Non-oncogene Addictionmentioning
confidence: 99%